TO THE QUESTION ON RAISING EFFICIENCY OF INSTRUMENTAL AND PROFESSIONAL PREPARATION OF FUTURE TEACHER OF MUSIC ON THE MODULE «SELF-DEPENDENT MUSIC MAKING» (Pedagogy of Higher and Secondary Education, 2007)
The article examines the essence of preparation of future teachers of music on the module «Self-Dependent Music Making», scientifically grounds and discovers methods that promote raising the efficiency of their formation.
Keywords: self-dependent music making; outline performance; module